ChemInform Abstract: Oxidative Annulation of Anilides with Internal Alkynes Using an (Electron‐Deficient η5‐Cyclopentadienyl)Rhodium(III) Catalyst under Ambient Conditions. Issue 42 (14th October 2014) - Hoshino, Yuki; Shibata, Yu; Tanaka, Ken
Abstract Optimized reaction conditions including a cyclopentadienyl rhodium catalyst and air as terminal oxidant are developed to allow the synthesis of a wide range of indole derivatives through oxidative annulation of anilides with internal alkynes.